2018
DOI: 10.1186/s12876-018-0895-7
|View full text |Cite
|
Sign up to set email alerts
|

One-day oral polyethylene glycol based cleanout is effective for pre-colonoscopy preparation in children

Abstract: BackgroundThe adequacy of pre-procedure preparation is the principal determinant of the quality of colonoscopy in pediatric as in adult patients. There is a lack of consensus, among providers on a standard pre-procedure regimen. Professional society guidelines include the use of Polyethylene glycol (PEG). Herein we report on the provider-assessed adequacy of a one day, age-categorized dosing, PEG based cleanout regimen in children undergoing colonoscopy in a tertiary institution.MethodsThe standard bowel prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Newer low-volume preparation alone (e.g., sodium picosulphate/magnesium citrate) or with combination with bisacodyl (e.g. PEG-bisacodyl) allows for preparation with only 2 L of solution instead of 4 L. Some of these preparations are officially approved for treatment of chronic constipation, and they have recently started to be used for bowel cleanout in children (PEG-3350) [3][4][5][6][7][8][9][10][11][12], whereas others are primarily used for colonoscopy cleansing but have no pediatric registration in Poland. The aim of this prospective, randomized, 3-arm study was to compare the efficacy, safety, and tolerability of three different 1-day regimens of bowel preparation for the pediatric colonoscopy: high-volume PEG-ELS versus low-volume PEG-3350 without electrolytes combined with bisacodyl versus sodium picosulphate/magnesium citrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer low-volume preparation alone (e.g., sodium picosulphate/magnesium citrate) or with combination with bisacodyl (e.g. PEG-bisacodyl) allows for preparation with only 2 L of solution instead of 4 L. Some of these preparations are officially approved for treatment of chronic constipation, and they have recently started to be used for bowel cleanout in children (PEG-3350) [3][4][5][6][7][8][9][10][11][12], whereas others are primarily used for colonoscopy cleansing but have no pediatric registration in Poland. The aim of this prospective, randomized, 3-arm study was to compare the efficacy, safety, and tolerability of three different 1-day regimens of bowel preparation for the pediatric colonoscopy: high-volume PEG-ELS versus low-volume PEG-3350 without electrolytes combined with bisacodyl versus sodium picosulphate/magnesium citrate.…”
Section: Discussionmentioning
confidence: 99%
“…No child needed to undergo lavage via a nasogastric tube. However, the rate of pediatric patients that are unable to ingest the prescribed amount of preparation varies from study to study [4,8,10,11,14]. Several factors may explain the high compliance rate with bowel cleansing protocols in our study.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Both senna and sodium phosphate can cause side effects, such as dehydration, which lead extra fluids intake to the patients. Furthermore, previous studies (9,28) have shown that PEG can be used as a safe and effective formulation for children at a dose of 1.5 g/kg for 4 days. However, it has been reported that bowel preparation should be ideally completed in a shorter period of time (12).…”
Section: Discussionmentioning
confidence: 99%
“…Phatak et al showed that 92–93% of 111 pediatric patients receiving 2 days of PEG with bisacodyl achieved “good” or “excellent” bowel preparation ( 18 ). A large two-part retrospective and prospective study of 656 patients on 1 day of oral PEG-3350 monotherapy reported adequate clean out (defined as thin or thick liquids) in 79.5 and 15.8% of cases, respectively ( 19 ). While the safety of PEG without electrolytes has been questioned, two studies reviewing electrolytes pre and post PEG-3350 did not show clinically significant changes in potassium or bicarbonate ( 17 , 20 ).…”
Section: Types Of Bowel Preparationmentioning
confidence: 99%